Uterine artery embolization in cervical pregnancy - alternative to total hysterectomy - Talshyn Ukybassova; Balkenzhe Imankulova; Dulat Tazhibayev; Bakhyt Abishev (National Scientific Medical Center, 2016)
In article experience of use of endovascular embolization of uterine arteries in treatment of cervical pregnancy is described. Super selective uterine artery embolization followed by removal of the ovum devascularization held 7 patients aged 27,8 ± 2,2 years with cervical pregnancy in terms of 5 and 7 weeks. After the reduction of level of chorionic gonadotropin, and in the absence of blood-groove in the fetal ovum, its evacuation was carried out under the control arteriography. Blood loss during the operation does not exceed 100 ml. Postoperative period lasted 4,6 ± 0,4 days. Thus, uterine artery embolization is effective method of complex treatment with cervical pregnancy thus reducing the risk of bleeding and to keep the reproductive function at young women.